THE EFFECTIVENESS OF THE BARK DREDGING OF THE JAVA WOOD TREE (LANNEA COROMANDELICA) ON THE DIABETIC ULCER HEALING PROCESS: BARK DREDGING OF THE JAVA WOOD TREE - Dwi Wulandari Ningtias Purnama; Wa Ode Rahmadania (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2021)
Background: Diabetic ulcer is a micro vascular complication that can be experienced by all DM patients. This condition necessitates appropriate wound care management to prevent infection, reduce necrotic tissue, and enhance the wound healing process. This study aims to determine the effect of using Javanese tree bark scraping on the healing process of diabetic ulcers, namely changes in the size of diabetic ulcers. Methods: This type of research is a Quasy Experiment with a Pre-test Post-test approach with control group. The populations in this study were all diabetic ulcer patients who came for wound care at Puskesmas Puuwatu totaling 16 respondents. Result: The results of statistical tests show that the p-value for the intervention group is 0.317 and the control group is 1,000, which means that there is no difference in wound size before and after the intervention in the intervention group and the control group. In the Mann Whitney statistical test, it was found that the p-value in the intervention group was 0.189, which is greater than the value of ? = 0.05. Conclusion: The dredging of the bark of the Java tree is not effective against changes in wound size in patients with diabetic ulcers.